Decreased risk of melanoma and nonmelanoma skin cancer in patients with vitiligo: a survey among 1307 patients and their partners. (21st December 2012) - Teulings, H.E.; Overkamp, M.; Ceylan, E.; Nieuweboer‐Krobotova, L.; Bos, J.D.; Nijsten, T.; Wolkerstorfer, A.W.; Luiten, R.M.; van der Veen, J.P.W.
Summary Background Vitiligo is a common skin disease characterized by autoimmune melanocyte destruction. Recent genetic studies suggest a lower susceptibility to melanoma in patients with vitiligo; however, lifetime melanoma prevalence in patients with vitiligo has not previously been studied. Nonmelanoma skin cancer (NMSC) prevalence has been studied, but only in small studies and with contradictory results. Objectives This retrospective, comparative cohort survey was designed to assess lifetime prevalences of melanoma and NMSC in patients with vitiligo compared with nonvitiligo controls. Methods Patients with nonsegmental vitiligo, who visited our clinic between January 1995 and September 2010, and were aged 50 years or older at the time of the study, were invited to participate in a postal survey. The questions regarded demographics, vitiligo characteristics, phototherapy history, skin cancer risk factors and the number of skin cancers experienced during the patient's lifetime. Patients were asked to have their partner fill in a control questionnaire. All skin cancers were validated by a pathology report. In total 2635 invitations were sent and 1307 eligible questionnaires were returned (50%). Multivariate logistic regression models were used to quantify adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for associations between vitiligo and lifetime prevalences of melanoma and NMSC. Results Adjusted for confounders, patients with vitiligo had a threefold lower probability of developing melanoma (adjusted OR 0·32; 95% CI 0·12–0·88) and NMSC (adjusted OR 0·28; 95% CI 0·16–0·50). Subgroup analyses of patients treated with narrowband ultraviolet (UV) B, and psoralen and UVA did not show dose‐related trends of increased age‐adjusted lifetime prevalence of melanoma or NMSC. Conclusions Our findings suggest that patients with vitiligo have a decreased risk of both melanoma and NMSC.